2004
DOI: 10.1007/s10311-003-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of pesticides by soil micro-organisms as a way of bound residues formation

Abstract: We studied the 14 C-tagged biochemical compartments such as proteins, lipids and polysaccharides from bacterial and fungal cultures supplied with 14 Cpesticides and 14 C-glucose. We showed that 14 C incorporation depends both on the substrate structure and on the nature of the micro-organism. Both bacterial and fungal cells incorporated glucose 14 C mainly into cell wall proteins. By contrast, glyphosate 14 C was mainly incorporated into cytoplasm carbohydrates by fungi. On the other hand, 2,4-dichlorophenoxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…This suggests that, while some of the 14 C was rapidly cycled through the organisms, some of the applied glyphosate could potentially be incorporated into more long‐lived fractions of the soil organic matter. Charnay et al 35 concluded that incorporation of herbicides into microbial biomass is an important step in the incorporation of herbicides into recalcitrant organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that, while some of the 14 C was rapidly cycled through the organisms, some of the applied glyphosate could potentially be incorporated into more long‐lived fractions of the soil organic matter. Charnay et al 35 concluded that incorporation of herbicides into microbial biomass is an important step in the incorporation of herbicides into recalcitrant organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the highest proportion of nonextractable residues detected in the S3 CR occurred simultaneously with the highest microbial activity. Charnay et al (2004) suggested that glyphosate was incorporated into the microbial cellular structure by metabolic activity.…”
Section: Carbon-14 Distribution Between Mineralized Extractable Andmentioning
confidence: 98%
“…Moreover, somewhat positive correlations ( P < 0.05) between bound metsulfuron‐methyl residues and soil MBC were found in the present study (Table 3), reinforcing the positive effect of soil microbial biomass and activity on degradation of the extractable residues. Previous studies showed that incorporation into soil microbial biomass was an important route in the formation of non‐extractable or bound residues for pesticides (Kaufman and Blake, 1970; Charney et al, 2004).…”
Section: Resultsmentioning
confidence: 99%